Anticipatory synergy adjustments: Preparing a quick action in an unknown direction - Zhou, Tao (2013)
We studied a mechanism of feed-forward control of a multi-finger action, namely anticipatory synergy adjustments (ASAs) prior to a quick force correction in response to a change in the gain of the visual feedback. Synergies were defined as co-varied across trials adjustments of commands to fingers that stabilized (decreased variance of) the total force. We hypothesized that ASAs would be highly sensitive to prior information about the timing of the action but not to information on its direction, i.e., on whether the gain would go up or down. The subjects produced accurate constant total force by pressing with four fingers on individual force sensors. The feedback signal could change from veridical (the sum of finger forces) to modified, with the middle finger force multiplied by 0.2 or by 1.8. The timing of the gain change and its direction could be known or unknown to the subject in advance. When the timing of the gain change was known, ASA was seen as a drop in the synergy index starting about 250–300 ms prior to the first visible correction of the total force. When the gain change timing was unknown, ASAs started much later, less than 100 ms prior to the total force correction. The magnitude of synergy index changes was significantly larger under the “time known” conditions. Information on the direction of the visual gain change had no effect on the ASA timing, while the ASA magnitude was somewhat larger when this information was not available to the subject. After the total force correction, the synergy index was significantly larger for the force signal computed using the modified gain values as compared to the synergy index value for the actual total force. We conclude that ASAs represent an important feed-forward motor control mechanism that allows preparing for a quick action even when the direction of the action is not known in advance. The results emphasize the subtle control of multi-finger synergies that are specific to the exact contributions of individual fingers to performance variables. The data fit well the central back-coupling hypothesis of synergies and the idea of control with referent body configurations.